Informal Micro-Enterprises and Solid Waste Collection: The Case Study of Addis Ababa - Mesfin Tilaye (Ethiopian Journal of the Social Sciences and Humanities, 2014)
Recently “embracing informality” is a notion advocated in urban centres of developing nations not only due to its unavoidable nature but also its contribution in providing service access to the marginalized, creating job opportunity to the urban poor and reducing cost to financially deprived municipalities. Involving informal sector as municipal service provider indeed requires the perception of stakeholders who are directly working with them. This research tried to have insight about the attitudes and perceptions that regulators, service users and providers have on the informality. Internal and external factors influencing service providers were also considered. The research used both Primary and secondary data sources. One hundred sixty micro-enterprise units were included in the survey. These account for about 35% of the total micro-enterprises available in the city. Stratified random sampling was employed based on the number and type of micro-enterprises available in each kebele (local government unit). Interview and focus group discussions were held with city officials at different levels and also community representatives. Secondary data sources used were research reports, government documents of relevant institutions as well as legal and policy documents. The findings suggest that there is an over all tendency to encourage solid waste collecting micro-enterprises on the part of the government. Flexibility and responsiveness were also opportunities secured by the users (households); the institutionalization process was not confined to the promotion of efficiency of the service and enhancement of business orientation.